Inactivation and recovery of sodium currents in cerebellar Purkinje neurons: evidence for two mechanisms. - Raman, I M (2001)
We examined the kinetics of voltage-dependent sodium currents in cerebellar Purkinje neurons using whole-cell recording from dissociated neurons. Unlike sodium currents in other cells, recovery from inactivation in Purkinje neurons is accompanied by a sizeable ionic current. Additionally, the extent and speed of recovery depend markedly on the voltage and duration of the prepulse that produces inactivation. Recovery is faster after brief, large depolarizations (e.g., 5 ms at +30 mV) than after long, smaller depolarizations (e.g., 100 ms at -30 mV). On repolarization to -40 mV following brief, large depolarizations, a resurgent sodium current rises and decays in parallel with partial, nonmonotonic recovery from inactivation. These phenomena can be explained by a model that incorporates two mechanisms of inactivation: a conventional mechanism, from which channels recover without conducting current, and a second mechanism, favored by brief, large depolarizations, from which channels recover by passing transiently through the open state. The second mechanism is consistent with voltage-dependent block of channels by a particle that can enter and exit only when channels are open. The sodium current flowing during recovery from this blocked state may depolarize cells immediately after an action potential, promoting the high-frequency firing typical of Purkinje neurons.